1995
DOI: 10.3109/02713689508998520
|View full text |Cite
|
Sign up to set email alerts
|

Localization of nerves adjacent to goblet cells in rat conjunctiva

Abstract: Neural stimulation of the cornea induces conjunctival goblet cell mucous secretion. Immunofluorescence microscopy was used to determine if nerves are present near conjunctival goblet cells and what types of nerves are present. In euthanized rats, the local anesthetic lidocaine (1%) was placed topically on the ocular surface for 10 min to prevent goblet cell mucous secretion. The ocular surface tissues were removed and either fixed in formaldehyde and then frozen, or frozen first and then post-fixed in formalde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
37
1
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 9 publications
0
37
1
1
Order By: Relevance
“…Likewise, an intercellular communication could be transmitted via gap junctions from directly innervated cells of the basal cell layer, as demonstrated experimentally in the corneal epithelium of rabbits (Williams and Watsky, 1997). In contrast to the present findings, other authors (Dartt et al, 1995(Dartt et al, , 1996 have described VIPimmunoreactive, nerve-like structures associated with goblet cells of the bulbar conjunctiva of the rat, however, no electron microscopic evidence was given. Conversely the possibility cannot be excluded that differences between two species exist.…”
Section: Discussioncontrasting
confidence: 53%
“…Likewise, an intercellular communication could be transmitted via gap junctions from directly innervated cells of the basal cell layer, as demonstrated experimentally in the corneal epithelium of rabbits (Williams and Watsky, 1997). In contrast to the present findings, other authors (Dartt et al, 1995(Dartt et al, , 1996 have described VIPimmunoreactive, nerve-like structures associated with goblet cells of the bulbar conjunctiva of the rat, however, no electron microscopic evidence was given. Conversely the possibility cannot be excluded that differences between two species exist.…”
Section: Discussioncontrasting
confidence: 53%
“…Our data suggest that decreased corneal sensation is associated with tear deficiency, abnormal impression cytologic results, and thinning of the cornea in KC. Dartt et al 22 showed that the nerves appear to be located around conjunctival goblet cells and could stimulate mucous secretion directly. Sensory neurotransmitters in the limbus or conjunctiva can be released antidromically by depolarization from activated sensory nerves in the central cornea in a process known as neurogenic irritation.…”
Section: Discussionmentioning
confidence: 98%
“…HSV-1 and HSV-2 demonstrate neuronal specificity for A5ϩ and IB4ϩ neurons, respectively, regardless of the route of infection. One-half of the LAT-positive latent HSV-1 reservoir is found in A5ϩ neurons, and one-half of the LAT-positive latent HSV-2 reservoir is found in IB4ϩ neurons, in the TG after ocular infection or in the DRG after genital infection (5)(6)(7)(8)(9). Thus, different patterns of HSV-1 and HSV-2 recurrence cannot be adequately explained by preferential establishment of latency in different types of sensory neurons.…”
mentioning
confidence: 93%
“…Sympathetic neurons of the superior cervical ganglia (SCG) and parasympathetic neurons in the ciliary ganglia (CG) innervate the conjunctival epithelium and stroma (6), and mixed autonomic neurons in the major pelvic ganglia (MPG) innervate the genitourinary tract. In both humans and animal models, HSV-1 and HSV-2 latent viral DNA has been detected in autonomic ganglia, including the SCG, CG, pterygopalatine ganglia (PTG), and MPG (also referred to as the paracervical ganglia) (7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%